Capacidade funcional de indivíduos com osteoartrite de joelho - Gomes, Luiz Henrique (2013)
Osteoarthritis is the articular disease more prevalent and also, the main cause of pain and inability in the elderly population. Objective: The current study aimed analyse the characteristics related to pain and functional ability of people with knee osteoarthritis. Materials and Methods: A transverse study was made with 16 carriers of the diagnosis of knee osteoarthritis treated at the Public Health Center (PHC) of Jau County, by using a multidimensional questionary containing demographic occupational variables and life habits and the Lequesne questionary for knee and hip osteoarthritis. Result: The majority of the participants was female, caucasian and 60 aged or older. Knee osteoarthitis participants,11( 68.81 ) said to have pain during night rest and 14 ( 87.51 ) said to have morning stiffness or pain that diminishes after getting up, and 12 ( 75% ) while walking. In relation to daily life activities 56.2% said having difficulty going up and down the stairs of a floor and 43.8% said to be incapable of crouching or kneeling, 50% showed difficulty to walk on irregular floor. Conlusion: Through this study, it was concluded that knee osteoarthritis is a disease which affects the functional ability of people and limit the performance of daily life activities, specially where movements of lower members are required like crouching, kneeling and going up and down the stairs